The Benefits of Fasting for the Physical and Mental Health of Grade 8 Students - Qotrunnada, Vitya; Waharjani, Waharjani (Early Publishing, 2026)
Fasting is a religious practice observed by Muslims around the world during the month of Ramadan. In addition to being a religious obligation, fasting also has many benefits for physical and mental health, especially for adolescents. This article aims to explore the benefits of fasting for the physical and mental health of eighth-grade students. Fasting is a practice often integrated into religious and cultural traditions, yet its specific impact on the developmental stage of early adolescents, requires further exploration. Objective: This study aims to analyze the physical and mental health benefits of fasting for Grade 8 students, focusing on metabolic changes and psychological well-being. Methods a qualitative approach with a library research method was employed, synthesizing data from various health journals and psychological reports related to adolescent fasting. Results: The findings indicate that fasting contributes to physical health by regulating metabolic processes, stabilizing cortisol levels, and improving sleep quality through circadian rhythm adjustment. Mentally, fasting is associated with increased self-control, reduced anxiety, and enhanced cognitive focus.Fasting provides significant holistic benefits for Grade 8 students, supporting both their physiological growth and emotional resilience. It is recommended that schools and parents provide proper nutritional guidance to maximize these benefits during fasting periods. The results show that fasting not only improves physical health through detoxification, but also provides mental benefits such as increased concentration, emotional control, and improved mental resilience.